Speed control analysis of brushless DC motor based on maximum amplitude DC current feedback - abu hassan, mohd arif; Abdullah, Abdul Rahim; Bahari, Norhazilina (EDP Sciences, 2014)
This paper describes an approach to develop accurate and simple current controlled modulation technique for brushless DC (BLDC) motor drive. The approach is applied to control phase current based on generation of quasi-square wave current by using only one current controller for the three phases. Unlike the vector control method which is complicated to be implemented, this simple current modulation technique presents advantages such as phase currents are kept in balance and the current is controlled through only one dc signal which represent maximum amplitude value of trapezoidal current (Imax). This technique is performed with Proportional Integral (PI) control algorithm and triangular carrier comparison method to generate Pulse Width Modulation (PWM) signal. In addition, the PI speed controller is incorporated with the current controller to perform desirable speed operation of non-overshoot response. The performance and functionality of the BLDC motor driver are verified via simulation by using MATLAB/SIMULINK. The simulation results show the developed control system performs desirable speed operation of non-overshoot and good current waveforms.